Territorial evidence supporting policy-making in Europe: How ESPON came, saw and conquered. Issue 2 (2nd April 2016) - Böhme, Kai
Abstract : In the 1990s there was a strong need for comparable territorial evidence to support the development of European spatial planning policies. This led to the establishment of the ESPON programme. ESPON is a success story. Today there is a strong body of comparable evidence on territorial development in Europe and this evidence influences policy-making at European level, in EU Member States, as well as at regional level. Still there is room for improvement and a constant demand for more and better evidence. Despite this, ESPON has achieved a level of maturity suggesting it might be time to take the next step. Going beyond providing input to policy processes, ESPON has the potential to establish itself as a platform for forward-thinking discussions about territorial development trends and policies.